PEMBERANTASAN PERDAGANGAN ORANG - Hotman Sitorus (Fakultas Hukum Universitas Kristen Indonesia, 2016)
Low No.21 of 2007 concerning the eradication of trafficking in person. Indonesia is not only the country of origin for trafficking in person but has become a country of destination and transit countries. This is because Indonesia is a strategic location. Victims of people trafficker channel for various purposes such as trafficked to be prostates, soldier, or are not in paid employment purpose of this paper is to fid out the delivery of children a broad. This research method is a normatif study research: birth urgency legislation specifically dealing with this as a result of the widespread network of organized crime card dis organized, both between countries, and within the country, country, and respect for rights human rights.Kata Kunci: Perdagangan Orang